Formation of New Words in the Uzbek Language and Their Representation in Dictionaries (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigates the formation of new words in the Uzbek language and their representation in dictionaries. It examines the morphological, semantic, and sociocultural mechanisms that contribute to neologism creation. The research highlights how technological innovations, social media, globalization, and youth culture accelerate the emergence and adoption of new lexical units. The study also emphasizes the role of dictionaries in standardizing and documenting neologisms, ensuring accurate usage in both spoken and written communication. Findings indicate that new word formation in Uzbek is dynamic, influenced by morphological productivity, compounding, borrowing, semantic shifts, and sociocultural trends. The results provide insights for linguists, educators, and lexicographers in understanding and supporting the evolving vocabulary of the Uzbek language.